Comparing Outcomes of Upper Extremity Brachiobasilic Arteriovenous Fistulas and Arteriovenous Grafts: A Systematic Review and Meta-Analysis. Issue 1 (January 2022) - Haddad, David J.; Jasty, Venkata Sai; Mohan, Babu; Hsu, Chiu-Hsieh; Chong, Chyi Chyi; Zhou, Wei; Tan, Tze-Woei
Objective: It is unclear what the optimal upper extremity hemodialysis access is for patients without a suitable cephalic vein for arteriovenous fistulas (AVFs). The objective of this systematic review and meta-analysis was to compare the outcomes for upper extremity transposed brachiobasilic AVFs (BBAVFs) and prosthetic arteriovenous grafts (AVGs). Methods: A systematic review was performed to identify all English publications and abstracts comparing the patency outcomes of upper extremity BBAVFs and AVGs (January 1st, 1994 to April 1st, 2020). The outcomes assessed were 1-year and 2-year primary and secondary patency rates. Pooled odds ratios (OR) were calculated using the random-effects model, and I 2 statistic was used to assess between-study variability. Results: Twenty-three studies examining 2799 patients were identified and included in the study. The 1-year primary patency rates (OR = 1.68, 95% CI 1.24–2.28, p = 0.001, I 2 = 69.40%) and 2-year primary patency rates (OR = 2.33, 95% CI 1.59–3.43, p < 0.001, I 2 = 68.26%) were significantly better for BBAVFs than AVGs. Compared to AVGs, the 1-year secondary patency rates (OR = 1.45, 95% CI 1.05–1.98, p = 0.022, I 2 = 56.64%) and 2-year secondary patency rates (OR = 1.93, 95% CI 1.39–2.68, p < 0.001, I 2 = 57.61%) were also significantly higher for BBAVFs. Conclusion: The outcomes for upper extremity BBAVFs appear to be consistently superior to prosthetic hemodialysis access. This analysis supports the preferential placement of BBAVFs over AVGs in patients with a suitable upper extremity basilic vein.